Das Neue Bauen and the Notion of A-Perspectival Space - Uwe Drost (Oz, 1991)
The dramatic changes in our lives and environment, in the whole nature of work, and in the forms of media, transport and intercommunication mean that architecture and urban design have to search for opponunities to provide the public with possibilities of identification and orientation of their lives. Such a request is an inquiry of notion and conscious concepts.